USGA 지반에 켄터키 블루그래스 조성 시 파종량 차이가 지상부 잔디생장 및 지하부 뿌리발달에 미치는 효과 - 김경남(Kyoung-Nam Kim) (Weon'ye gwahag gi'sulji, 2023)
USGA 모래 지반에 켄터키 블루그래스 종자 파종 후 조성 1년차 시공단계에서 지상부 잔디생장 및 지하부 뿌리발달에 최적인 파종량 수준을 규명하고자 시작하였다. 공시 파종 처리구는 전체 5 수준의 파종량(VLS 6g, LS 9g, MS 12g, HS 15g, VHS 18g·m-2)으로 하였으며, 시험구는 난괴법 4반복으로 배치하였다. 지상부 잔디생장과 뿌리발달 차이를 비교하기 위해서 잔디엽색, 품질 및 뿌리 길이를 2009년 5월부터 12월까지 연중 조사하였다. 이러한 생육 특성은 파종 후 시간이 경과함에 따라 증가하였으며, 파종량에 따라 처리구간 차이가 나타났다. 잔디색상은 초기 시공 단계인 3개월 동안은 VHS 파종구, 그리고 3개월이후에는 HS 파종구가 가장 양호하였다. 잔디품질은 초기 약 5개월은 VHS 파종구, 그리고 5개월 이후에는 HS 파종구가 좀 더 우수한 경향으로 나타났다. 하지만 지상부 생장특성과 다르게 지하부 뿌리발달은 파종량이 낮을수록 양호하였고, 파종량이높을수록 불량하게 나타났다. 따라서 잔디밭 조성 1년차 시공단계에서 뿌리생장은 파종량이 9g·m-2 이하인 VLS 및 LS 파종구가 가장 우수하였으며, 파종량이 15g·m-2 이상인 HS 및 VHS 파종구는 실험기간 내내 저조하였다. 즉 조성 1년차 시공단계의 적정 파종량은 지상부 생장관점에서 잔디색상 및 품질 위주로 판단 시 15–18g·m-2 사이가 양호하였지만, 지하부 생장관점에서 뿌리발달 위주로 판단할 경우에는 6–9g·m-2 사이가 더 적절하였다. 향후 잔디밭 성숙 단계인 2년차에 데이터 수집을 통해 지상부 및 지하부 조직의 생육 특성 변화를 비교할 수 있다면 장기적으로 잔디품질과 내구성이 우수한 고품질 잔디밭 조성및 유지 관리에 도움이 될 것이다. This research was initiated to investigate the effects of seeding rates on top and root growth characteristics in Kentucky bluegrass (KB, Poa pratensis L.) under the USGA (United States Golf Association) soil system and to provide practical information on proper KB seeding rates. Treatments were comprised of the following five seeding rates: VLS (6 g·m-2), LS (9 g·m-2), MS (12 g·m-2), HS (15 g·m-2) and VHS (18 g·m-2). Each treatment was replicated four times in a randomized complete block design. Visual turfgrass color, turf quality and root growth were measured from May to December in 2009. Thesse growth characteristics varied with seeding rate and increased with month after seeding (MAS). Evaluation in the establishment phase indicated that the best color was associated with VHS until 3 MAS, but with HS after that. The turf quality rating score was greatest with VHS until 5 MAS, but with HS after that. Data on root growth, however, showed opposite responses as compared with those of top growth characteristics. During the study, the lower the seeding rate, the longer the root length. Therefore, the best root growth performances were associated with LS and VLS, while HS and VHS, in which the seeding rate was over 15 g·m-2, showed poor performances. In the first-year establishment phase, optimum seeding rates in KB are between 15 and 18 g·m-2 in regards to turfgrass color and quality. However, in terms of root growth, they are in the range of 6 to 9 g·m-2. Further data analysis in a mature-phase will be a practical necessity for the best turfgrass quality and sustainable performance on high-quality sports turf design, construction and management. KCI Citation Count: 1